2020
DOI: 10.1038/s41598-020-79136-x
|View full text |Cite
|
Sign up to set email alerts
|

Coefficient of variation as an image-intensity metric for cytoskeleton bundling

Abstract: The evaluation of cytoskeletal bundling is a fundamental experimental method in the field of cell biology. Although the skewness of the pixel intensity distribution derived from fluorescently-labeled cytoskeletons has been widely used as a metric to evaluate the degree of bundling in digital microscopy images, its versatility has not been fully validated. Here, we applied the coefficient of variation (CV) of intensity values as an alternative metric, and compared its performance with skewness. In synthetic ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…For bundling indices, we were interested in their level of conformity because direct indices (based on binary shape) and indirect indices (based on brightness frequency distribution) are entirely different strategies to measure bundling. Using the same approach of correlation analysis, we found that diameter_TDT and diameter_SDT display strong positive correlation, while skewness and CV have merely medium-low correlation, which echoes the previous report demonstrating skewness and CV have different performance on the bundling evaluation 20 .…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…For bundling indices, we were interested in their level of conformity because direct indices (based on binary shape) and indirect indices (based on brightness frequency distribution) are entirely different strategies to measure bundling. Using the same approach of correlation analysis, we found that diameter_TDT and diameter_SDT display strong positive correlation, while skewness and CV have merely medium-low correlation, which echoes the previous report demonstrating skewness and CV have different performance on the bundling evaluation 20 .…”
Section: Resultssupporting
confidence: 84%
“…Through the image processing pipeline, cytoskeletal indices were automatically calculated from the binary image generated by ILEE. As a substantial expansion from three previously defined cytoskeletal indices (e.g., occupancy, skewness , and CV ) 17,20 , we totally introduced 12 indices (Fig. 1a); particularly, we focused on 9 of the 12 indices in this study, as they are normalized and ready for biological interpretation (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 B and Video 1 ). Quantification of the spatial organization, by measuring anisotropy using FibrilTool ( Boudaoud et al, 2014 ), and coefficient of variation (CV; Higaki et al, 2020 ), which is an indicator of cytoskeleton bundling, further confirmed that ScMreB5 E134A exhibited differences in bundling of filaments ( Fig. 4, C and D ).…”
Section: Resultsmentioning
confidence: 59%
“…To eliminate the influence of the rice cluster density, this paper adopted the coefficient of variation (CV) as a heterogeneity index for evaluating the heterogeneity in the rice cluster distribution in the region of interest 29 . where is the area of the region occupied by the rice clusters, is the number of rice clusters, is the mean.…”
Section: Methodsmentioning
confidence: 99%